The duality of gaze: eyes extract and signal social information during sustained cooperative and competitive dyadic gaze - Jarick, Michelle; Kingstone, Alan (Frontiers in Psychology, 2015)
In contrast to non-human primate eyes, which have a dark sclera surrounding a dark iris, human eyes have a white sclera that surrounds a dark iris. This high contrast morphology allows humans to determine quickly and easily where others are looking and infer what they are attending to. In recent years an enormous body of work has used photos and schematic images of faces to study these aspects of social attention, e.g., the selection of the eyes of others and the shift of attention to where those eyes are directed. However, evolutionary theory holds that humans did not develop a high contrast morphology simply to use the eyes of others as attentional cues; rather they sacrificed camouflage for communication, that is, to signal their thoughts and intentions to others. In the present study we demonstrate the importance of this by taking as our starting point the hypothesis that a cornerstone of non-verbal communication is the eye contact between individuals and the time that it is held. In a single simple study we show experimentally that the effect of eye contact can be quickly and profoundly altered merely by having participants, who had never met before, play a game in a cooperative or competitive manner. After the game participants were asked to make eye contact for a prolonged period of time (10 min). Those who had played the game cooperatively found this terribly difficult to do, repeatedly talking and breaking gaze. In contrast, those who had played the game competitively were able to stare quietly at each other for a sustained period. Collectively these data demonstrate that when looking at the eyes of a real person one both acquires and signals information to the other person. This duality of gaze is critical to non-verbal communication, with the nature of that communication shaped by the relationship between individuals, e.g., cooperative or competitive.